The Persistence Of Malaysian Unit Trusts Performance By Using Odds Ratio Analysis - Amir, Afizar (2005)
This study seeks to analyze the persistency of Malaysian unit trusts for the long term periods. The period measured was from January 1995 to December 2004. The main focus is to explore whether there is persistency of performance either positive (hot hand or cold hand) or negative (reversed) persistence among Malaysian unit trusts. Indeed, the persistency performance also will be measured by different benchmarks with various intervals of time.